What do we know about zakat literature? A bibliometric review - M. Alshater, Muneer; Saad, Ram Al Jaffri; Abd. Wahab, Norazlina; Saba, Irum (Emerald Group Publishing Limited, 2021)
Abstract Purpose – This paper aims to develop a meaningful single-source reference for Islamic economics and finance scholars concerning zakat intellectual structure published in journals indexed by the Scopus database. Design/methodology/approach – The bibliometric method is used to describe and analyze the evolution of publication structure and its various co-relations such as co-citation, co-authorship and bibliographical coupling. Findings – The authors discuss the influential and conceptual aspects of the published literature on zakat. An interesting finding is that few papers have received more than 50 citations. The analysis revealed that the Journal of Islamic Accounting and Business Research is the most cited source. Nevertheless, the list of the eight most cited papers reflects that research in this field is still dearth. Further, the authors find that zakat is discussed within the context of religion, its institutional framework, its role to eradicate poverty and distribution management of zakat. The authors also identify and present 14 research directions that will further stimulate scholarly work in the zakat field. Research limitations/implications – The study confines on English papers and reviews published in journals indexed by the Scopus database only; hence, the study is representative of the moderate and high-quality papers published in this area of knowledge. Practical implications – Researchers envision that this bibliometric study will complement metanalysis and qualitative structured literature reviews as a method of reviewing and evaluating the scientific literature of this study area; thus, this may help researchers for futuristic research directions. Originality/value – To the best of the authors’ knowledge, this paper is the first to tackle the zakat area from a bibliometric aspect. The authors believe that this will help scholars and researchers to stand on firm bases regarding the scientific development of this area of study.